A rare case of direct cervical skin involvement from metastatic cervical lymph node in carcinoma of oral cavity - Lakshmi Narayana, M.; Swetha, V.; Kumarguru, B. N. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Carcinoma of the oral cavity is becoming more prevalent in India owing to increased betel nut chewing, beedi smoking, consumption of hans, gutka and other tobacco products. In the tumor spread, first it metastasizes to cervical nodes and then to distant sites. We report a rare case of direct skin involvement from metastatic cervical lymphadenopathy. A 60 years old lady came with the complaints of swelling on the left side of the neck since 3 years. She was a betel nut chewer since childhood. On examination, the swelling was tender, firm, fungating with erythema over the swelling. Oral cavity examination showed a 2×3 cm ulcerative growth in the left gingivobuccal sulcus with grade III trismus. CECT scan showed irregular heterogeneously enhancing necrotic mass of size 5.1×4.2×3.7 cm, in the submandibular region showing skin infiltration. There was an irregular heterogeneously enhancing lesion in the left gingivobuccal sulcus. Biopsy from the growth showed features of well-differentiated squamous cell carcinoma. The patient underwent composite resection and left modified radical neck dissection with complete excision of the fungating tumor with tumor-free margins. The defect in the oral cavity and neck was closed with pectoralis major myocutaneous flap and deltopectoral flap. Histopathology showed pT2N3bM0 with stage IVb and patient was advised adjuvant chemo-radiation. In conclusion, cervical skin involvement from cervical metastasis is rare compared to facial skin involvement from the tumor. Patients with N3b nodal staging should be planned in a multidisciplinary setting for a better treatment outcome.